PERLINDUNGAN HUKUM TERHADAP PELAKU TINDAK PIDANA MEMBERIKAN HAK PILIH LEBIH SATU KALI PILKADA 2017 DI KABUPATEN ACEH BARAT - Muhammad Yunus; Phoenna Ath Thariq; Nila Trisna; Muhammad Nasir (Ius Civile: Refleksi Penegakan Hukum dan Keadilan, 2021)
Every Indonesian citizen actually has the same rights before the law. Likewise, the perpetrators of criminal acts get treatment in accordance with the capacity of the acts committed. Legal protection does not really focus on welfare, but rather on the determination of the consequences of a legal event. This is outlined in the 1945 Constitution Article 27 Paragraph 1. Responding to the paradigm of thinking about the perpetrators of criminal offenses should get the maximum punishment, it does not mean to impose a sentence that exceeds the legal capacity in force in the country. this also applies to the double cast in the 2017 regional elections which took place in the District of West Aceh. The mechanism of the process of legal protection for perpetrators of criminal acts, is part of legal efforts in ensuring justice with legal certainty for the benefit of the law through formal and or material stages. Law Number 16 of 2011 concerning Legal Aid and Law Number 39 of 1999 concerning Human Rights is a form of the state's seriousness in guaranteeing the constitutional rights of each of its citizens to obtain recognition, guarantees, protection and fair legal certainty and equal treatment. before the law. Keywords: Protection, Law, West Aceh